Hydrogen etching on the surface of GaN for producing patterned structures - Yeh, Yen-Hsien; Chen, Kuei-Ming; Wu, Yin-Hao; Hsu, Ying-Chia; Lee, Wei-I (My University, 2011)
The morphology of GaN etched in hydrogen atmosphere is investigated. It is found that GaN surfaces have different profiles after being etched at different pressures. The profile resembles a surface that has been decorated with columns or mooring posts at high pressure and with deep cavities at low pressure. Etch pit density (EPD) experiment shows all dislocations have been etched to form cavities at low pressure, but not all the cavities result from etched dislocations. A model has been developed to explain the mechanism of H(2) etching. Patterned structure with a flat surface and porous inside has been produced by two-step etching which is designed according to the model. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Hydrogen etching; Surface processes; Surface structure; Hydride vapor phase epitaxy; Nitrides; Semiconducting III-V materials